If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 4 + 60 = 10 + 15x Reorder the terms: 4 + 60 + 6x = 10 + 15x Combine like terms: 4 + 60 = 64 64 + 6x = 10 + 15x Solving 64 + 6x = 10 + 15x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-15x' to each side of the equation. 64 + 6x + -15x = 10 + 15x + -15x Combine like terms: 6x + -15x = -9x 64 + -9x = 10 + 15x + -15x Combine like terms: 15x + -15x = 0 64 + -9x = 10 + 0 64 + -9x = 10 Add '-64' to each side of the equation. 64 + -64 + -9x = 10 + -64 Combine like terms: 64 + -64 = 0 0 + -9x = 10 + -64 -9x = 10 + -64 Combine like terms: 10 + -64 = -54 -9x = -54 Divide each side by '-9'. x = 6 Simplifying x = 6
| -4x+4=-4(2y+6) | | 8-7x=9+6x | | -5x=ax-3b | | 5-8x=9x+3 | | 17+8x=3x+7 | | 6x-3(4x+2)=-3x-4 | | 3y-12=2(y+3) | | 5y-y=3y-4 | | -16x-12=-2x-60 | | 4x^2+4x-22=6-5x | | 7x-5=3+x | | 2(2w+6)=28 | | 4+2y=-8 | | 9x-6=6x-3 | | 9x-6=6-3 | | -16x-12=-2-60 | | 6x-8=27+6 | | 43-3f=f+9 | | 4x+x-6=19 | | y=9(x+2) | | 3x+2x-6=-2+x | | 18a+6b-4a-b= | | M=p(1+i)n | | x+9=9-x | | 9=2+b+2 | | 4v-10=18 | | 9x+4+139=44x+3 | | 8x=28+4 | | =9x+(x-3)*2+6 | | w(a-4)=2(q+5) | | 0=16t^2+32+32 | | 3x-31=2 |